Training on The Importance of Mastering Mandarin for High School Students at IT Khairul Imam - Devi Alvionita Alindra; Feby Yoana Siregar (RECORD: Journal of Loyality and Community Development, 2024)
In an increasingly interconnected world, linguistic proficiency, especially in Mandarin Chinese, holds significant value for high school students at IT Khairul Imam. Mandarin, a globally spoken language, serves as a gateway to China’s dynamic economy, providing students with cognitive, academic, professional, and cultural benefits. Research indicates that learning a second language enhances cognitive abilities such as problem-solving, creativity, and memory, leading to higher academic achievement. Mandarin proficiency also opens career opportunities, giving students a competitive edge in the global job market, particularly in international business, technology, and diplomacy. Additionally, learning Mandarin enriches students' cultural perspectives by deepening their understanding of Chinese history and traditions, fostering a more inclusive worldview. The methods implemented include integrating Mandarin classes into the curriculum with qualified instructors and organizing extracurricular activities like language clubs and competitions. These activities provide practical language practice in informal settings, enhancing students’ proficiency and engagement. The results highlight the positive impact of these methods on students' cognitive development, career prospects, and cultural understanding. In conclusion, the Mandarin program at IT Khairul Imam is a strategic investment in students’ futures. It aligns with national educational goals and emphasizes comprehensive education, preparing students for real-world challenges. Mastering Mandarin equips students with essential skills for navigating a globalized world, making it a crucial component of their academic and personal development.